The Effect of the Retroperitoneal Transpsoas Minimally Invasive Lateral Interbody Fusion on Segmental and Regional Lumbar Lordosis. (2nd August 2012) - Le, Tien V.; Vivas, Andrew C.; Dakwar, Elias; Baaj, Ali A.; Uribe, Juan S.
Abstract : Background . The minimally invasive lateral interbody fusion (MIS LIF) in the lumbar spine can correct coronal Cobb angles, but the effect on sagittal plane correction is unclear. Methods . A retrospective review of thirty-five patients with lumbar degenerative disease who underwent MIS LIF without supplemental posterior instrumentation was undertaken to study the radiographic effect on the restoration of segmental and regional lumbar lordosis using the Cobb angles on pre- and postoperative radiographs. Mean disc height changes were also measured. Results . The mean follow-up period was 13.3 months. Fifty total levels were fused with a mean of 1.42 levels fused per patient. Mean segmental Cobb angle increased from 11.10° to 13.61° (P < 0.001 ) or 22.6%. L2-3 had the greatest proportional increase in segmental lordosis. Mean regional Cobb angle increased from 52.47° to 53.45° (P = 0.392 ). Mean disc height increased from 6.50 mm to 10.04 mm (P < 0.001 ) or 54.5%. Conclusions . The MIS LIF improves segmental lordosis and disc height in the lumbar spine but not regional lumbar lordosis. Anterior longitudinal ligament sectioning and/or the addition of a more lordotic implant may be necessary in cases where significant increases in regional lumbar lordosis are desired.